Problem Solving Strategies Learning In Hindu Concepts In The Society Era 5.0 - Utari Dewi, Komang Sri (Metta : Jurnal Ilmu Multidisiplin, 2022)
The era of Society 5.0 brought significant developments to the world of education.  Teachers and the community must be skilled and have adequate abilities in welcoming the era of society 5.0. Infrastructure, human resource development (HR), synchronization between the world of education and the use of technology, these four things have a major role in entering the era of sociaty that will create qualified graduates. This paper aims to provide an overview of learning using the Hindu concept in the Era of Society 5.0 in an effort to solve learning problems, increase student interest and motivation. This research uses a descriptive Qualitative research method because based on literature studies using literacy such as books, journals and other research. In this paper, it is described about 1) learning problems caused by external and internal factors, 2) in the Era of Society educators become mobilizers, have qualified abilities in the digital field, and think creatively, 3) Learning strategies according to Hindu concepts used by PAIKEM which are then elaborated with the Sad Darsana concept which can also be used as an alternative way to solve problems in learning, among others: Dharma Wacana Strategy, Dharmagītā Strategy, Dharma Tula Strategy, Dharma Yatra Strategy, Dharma Shanti Strategy, Dharma Sadhana Strategy.